2017
DOI: 10.1021/acsomega.7b00236
|View full text |Cite
|
Sign up to set email alerts
|

N-Geminal P/Al Lewis Pair–Alkyne Dipolar Cycloaddition to the Zwitterionic C2PNAl-Heterocyclopentene

Abstract: The N-geminal P/Al Lewis pair [Ph 2 PN(2,6- i Pr 2 C 6 H 3 )AlEt 2 ] 2 ( 1 ) has been prepared and studied for reaction with a series of alkynes. The reaction of 1 with RC≡CR yielded zwitterionic C 2 PNAl-heterocyclopentene [Ph 2 ⌜ PN(2,6- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Importantly, the terminal alkynes undergo 1,2‐addition, in contrast to the typically observed acid‐base reaction path . Such 1,2‐reactivity of alkynes was also found for geminal aluminum/phosphorus and gallium/phosphorus FLPs.…”
Section: Group 13 Element‐ligand Cooperativitymentioning
confidence: 68%
“…Importantly, the terminal alkynes undergo 1,2‐addition, in contrast to the typically observed acid‐base reaction path . Such 1,2‐reactivity of alkynes was also found for geminal aluminum/phosphorus and gallium/phosphorus FLPs.…”
Section: Group 13 Element‐ligand Cooperativitymentioning
confidence: 68%
“…The latter shifts are only about 10 ppm downfield from those of the other Al phosphinimine-amidinato complex previously reported, [Al-{κ 2 -N,N′-(N i Pr)C(N i Pr)(PPh 2 NDipp)}Et 2 ]. 5 The 1 H and 13 C{ 1 H} NMR spectra of 3a−c denote the presence of a symmetry plane, which is defined by the five-membered AlNCPN metallacycle, thus accounting for the same number of resonances as those found for compounds 2a−c in both spectra. The AlMe 2 fragment for compounds 3a−c originates slightly downfield singlet resonances in both spectra when compared to those in 2a−c in the range −0.01 to −0.07 ppm in the 1 H NMR spectra, and ca.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The potential interest in devising efficient synthetic procedures to prepare new κ 2 -N,N′-phosphinimine-amidinato complexes stems from (i) the paucity of examples found in the literature, the only ones being another Al complex of formula [Al{κ 2 -N,N′-(N i Pr)C(N i Pr)(PPh 2 NDipp)}Et 2 ] 5 and phosphinimineimidazolate derivatives of Na and Rh, 6 and (ii) the fact that conventional synthetic routes to these derivatives usually involve the use of hazardous chemicals, such as organic azides, and multistep processes. 6 As a follow-up to our previous communication, and to attest the scope of the aforementioned ligand rearrangement reaction for the synthesis of new phosphinimine-amidinato compounds, in this full paper we study the reactivity of three Nphosphinoguanidines (one of them reported for the first time, the cyclohexyl derivative (HNCy)(Ph 2 PNCy)C(NDipp) (1c)) toward the following four metal alkyls: the already mentioned AlMe 3 and ZnEt 2 as well as two s-block compounds, Mg n Bu 2 and n BuLi.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complexes of the formula R2AlPR2, such as the landmark Trip2AlP(SiPh3)Ad (CXLI, Figure 103), 268 are relatively uncommon 269 and almost all have not had any significant reactivity studies published on them. Recently the reactivity of aluminium phosphine complexes has been centred around their use as FLPs, with bridged R2P-X-AlR2 (X = C,N) complexes such as CXLII being used to activate alkynes, 270 alkenes, 271 isocyanates, [271][272][273] CO2, [271][272][273][274] and H2. 247…”
Section: Reactivity Of Aluminium Phosphanidesmentioning
confidence: 99%